The Effect of the Predict – Observe - Explain (Poe) on Critical Thinking Skills in Science Education : A Quasi-Experimental Study With Fifth-Grade Students - Fuadliyah, Aslikhatul; Yasin, Fajar Nur (Papanda Publisher, 2025)
This research is motivated by the low critical thinking skills of students, as evidenced by low learning outcomes and students who are less actively involved in learning. This study aims to analyze the influence of the Prediction, Observation, Explanation (POE) learning model on the critical thinking skills of the material on the properties of light in the Natural and Social Sciences subject of students at SDN Tanjungsari 1 for one week. The sample of this research was class B as the experimental class and class A totaling 21 as the control class. Type of Quasi Experimental research with Pretest Posttest Control Group Design. The data collection technique used in this study is a test. This research instrument uses 7 questions to adjust the critical thinking indicators and teacher observation sheets. Based on the data analysis, it can be seen that there is an influence of the POE learning model on the critical thinking skills of students at SDN Tanjungsari 1. This is evidenced by the results of the t-test analysis at a significance level of 5% obtained a sig value of 2 tailed 0.014 <0.05 and tcount 2.579 and ttable 2.483 so it can be concluded that 2.579> 2.483 or tcount> ttable then Ha is accepted. Thus, the POE model is an alternative solution in improving the critical thinking skills of students in the material on the properties of light in class V SDN Tanjungsari 1.